Assessing parent–child interaction in infant deafness. Issue 3 (June 2021) - Curtin, Martina; Herman, Ros; Cruice, Madeline; Morgan, Gary
Abstract : Purpose of review: To highlight the importance of parent–child interaction (PCI) in infant deafness and address the lack of robust assessment tools in clinical practice. Recent findings: Most deaf babies are born to hearing parents with little experience in deafness. Deafness can reduce access to spoken language. Despite advancements in amplification technology, deaf children still present with delays in attention and communication skills at the start of nursery. Research reports that hearing parents of deaf infants can be more directive during interaction, spend less time following the child's focus of attention, and have more difficulty achieving successful turn-taking in conversation. Much research tells us that these factors impact on the quality and quantity of PCI. Good PCI, in all infants, but especially so in deafness, is a strong predictor of child language outcomes. Teachers of the Deaf and Speech and Language Therapists are the first professionals to support families in the home. For these professionals, having an objective way of assessing PCI would greatly assist and standardise their practice. However, to date, there are no deaf-specific assessments to observe and appraise a parent's communication behaviours when interacting with their deaf child. Summary: Intervention studies with families of deaf children have shown success in improving parental sensitivity and facilitative language techniques. An observational assessment in parent–deaf child interaction would ensure that communication interventions are appropriately targeted on the individual family's needs.